2015
DOI: 10.3109/09638288.2015.1073371
|View full text |Cite
|
Sign up to set email alerts
|

The current implementation status of the integration of sports and physical activity into Dutch rehabilitation care

Abstract: 37Purpose: To describe the current status of the nationwide implementation process 38 of a sports and physical activity stimulation programme to gain insight into how 39 sports and physical activity were integrated into Dutch rehabilitation care. 40 Methods:The current implementation status of a sports and physical activity 41 stimulation programme in 12 rehabilitation centres and 5 hospitals with a 42 rehabilitation department was described by scoring fidelity and satisfaction. 71 43Rehabilitation professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…In Dutch rehabilitation care, most rehabilitation centres and some hospital rehabilitation departments include "sports therapy" as a separate field in rehabilitation care, which has the responsibility to embed sports and physical activities into rehabilitation (1). However, the current study showed that some professionals experienced a lack of support from physiotherapists to embed physical activities into rehabilitation.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…In Dutch rehabilitation care, most rehabilitation centres and some hospital rehabilitation departments include "sports therapy" as a separate field in rehabilitation care, which has the responsibility to embed sports and physical activities into rehabilitation (1). However, the current study showed that some professionals experienced a lack of support from physiotherapists to embed physical activities into rehabilitation.…”
Section: Discussionmentioning
confidence: 66%
“…From the involved organizations (n = 18), all project leaders and a selection of counsellors were invited to participate in a semistructured interview by researcher FH. Counsellors were selected to participate if they were actively involved in the implementation 1 Stichting Onbeperkt Sportief, this national organization aimed for a larger participation within disabled sports and physical activity and the development of suitable and accessible sports facilities. From January 2016, Stichting Onbeperkt Sportief became part of Knowledge Center for Sport Netherlands.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activity Coach þ was designed for adults with a physical disability due to a physical impairment (e.g., brain injury, orthopaedic conditions) or a chronic disease that impairs mobility (e.g., cardiopulmonary disease, chronic pain, diabetes). Participants were included if they were 18 years or older, able to visit a primary healthcare physiotherapist, and were at least one year postrehabilitation or not familiar with rehabilitation in order to prevent overlap with an existing intervention during and directly after inpatient rehabilitation [25]. Participants of Activity Coach þ were asked to voluntarily participate in research by the activity coach during the first contact by phone.…”
Section: Participantsmentioning
confidence: 99%
“…Rimmer and Lai [8] present the Transformative Exercise Framework to support people with disabilities to transition from being patient to participant and from perceiving exercise as a mode of rehabilitation into means for wellness. Hoekstra et al [9] described the current state of affairs regarding integration of sports and physical activity in rehabilitation care in the Netherlands, indicating that promising steps are being made but also indicating room for improvement. Martin Ginis et al [10] signified the role of psychosocial factors for engaging in leisure time physical activities.…”
Section: Special Issue Editorialmentioning
confidence: 99%